2006
DOI: 10.1007/s10787-006-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Lafutidine can improve the quality of gastric ulcer healing in humans: a randomized, controlled, multicenter trial

Abstract: Improving the quality of ulcer healing (QOUH) is one of the valid methods of prevention of relapse of gastric ulcers. We investigated the effect of lafutidine on the QOUH of gastric ulcer compared with famotidine in a randomized, multi-centre controlled trial. Consecutive 80 patients with a gastric ulcer were randomly assigned to receive twice daily either lafutidine (10 mg) or famotidine (20 mg) for 12 weeks. Esophagogastroduodenoscopy was performed to examine the ulcer healing rate and rate of flat type ulce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Endoscopy was performed before and 8 weeks after initiation of treatment to check the quality of ulcer healing (QOUH). During endoscopy at 8 weeks, QOUH was classified as a flat or non‐flat pattern by means of indigo carmine staining 10–12 . Subjective and objective symptoms (epigastralgia, bloating sensation, anorexia, heartburn, nausea, vomiting, tenderness epigastric) were evaluated using four grades: absent (−), mild (+), moderate (++) and severe (+++).…”
Section: Methodsmentioning
confidence: 99%
“…Endoscopy was performed before and 8 weeks after initiation of treatment to check the quality of ulcer healing (QOUH). During endoscopy at 8 weeks, QOUH was classified as a flat or non‐flat pattern by means of indigo carmine staining 10–12 . Subjective and objective symptoms (epigastralgia, bloating sensation, anorexia, heartburn, nausea, vomiting, tenderness epigastric) were evaluated using four grades: absent (−), mild (+), moderate (++) and severe (+++).…”
Section: Methodsmentioning
confidence: 99%
“…A PPI was administered 30 min before indomethacin administration: omeprazole (30, 100 mg/kg), lansoprazole (30, 100 mg/kg), or rabeprazole (30, 100 mg/kg). The following were administered twice-30 min before and 6 h after indomethacin administration: an H 2 receptor antagonist (famotidine (3, 10 mg/kg), cimetidine (100 mg/kg), lafutidine [50] (30 mg/kg), or roxatidine [51] (60, 100, 200 mg/kg)); a mucosal protective agent (teprenone [52] (100, 300 mg/kg), rebamipide [53] (100, 300 mg/kg), irsogladine [54] (1, 10 mg/kg), ecabet sodium [55] (300 mg/kg)); sucralfate (500 mg/kg) or a PG analog (misoprostol (0.1 mg/kg)).…”
Section: Prevention and Treatment Of Small Intestinal Mucosal Injury mentioning
confidence: 99%
“…22 Although comparison studies using various H2 antagonists in drug-induced weight gain are not present currently, the agents ranitidine, famotidine and nizatidine have been found to have comparable efficacy in their usual doses used to treat peptic ulcer disease. 31,32 Thus, mechanisms other than H2 receptor antagonism could be involved in weight gain. Kroeze et al 33 found that the most robust predictor of a drug's propensity to increase weight was its affinity for the H1 receptor.…”
Section: Discussionmentioning
confidence: 99%